The Change of Intra-cerebral CST Location during Childhood and Adolescence; Diffusion Tensor Tractography Study - Kwon, Yong M.; Kwon, Hyeok G.; Rose, Jessica; Son, Su M. (Frontiers in Human Neuroscience, 2016)
Objectives: Corticospinal tract (CST) is the most important tract in motor control. However, there was no study about the change of CST location with aging. In this study, using diffusion tensor tractography (DTT), we attempted to investigate the change of CST location at cortex, corona radiata (CR) and posterior limb of internal capsule (IC) level with aging in typically developing children. Methods: We recruited 76 healthy pediatric subjects (range; 0-19 years). According to the result of DTT, the location of CST at cortex level was classified as follows; prefrontal (PFC), PFC with Premotor cortex (PMC), PMC, PMC with primary motor cortex (M1), M1, M1 with Primary sensory cortex (S1). Anterior-posterior location (%) of CSTs at CR and IC level was also assessed. Results: DTT results about CSTs of 152 hemispheres from 76 subjects were obtained. The most common location of CST projection was M1 area (58.6%) including PMC with M1 (25.7%), M1 (17.8%), and M1 with S1 (15.1%). The mean age of the projection of CST showed considerably younger at anterior cortex than posterior; (PFC; 4.12 years, PFC with PMC; 6.41 years, PMC; 6.72 years, PMC with M1; 9.75 years, M1; 9.85 years, M1 with S1; 12.99 years, S1; 13.75 years). Spearman correlation showed positive correlation between age and the location of CST from anterior to posterior brain cortex (r=0.368). Conclusions: We demonstrated that the location of CST projection is different with aging. The result of this study can provide the scientific insight to the maturation study in human brain.